Comprehensive analysis of karyopherin alpha family expression in lung adenocarcinoma: Association with prognostic value and immune homeostasis - Xiuwen Lan; Lin Zhao; Jian Zhang; Yingchun Shao; Yunmeng Qv; Jian Huang; Li Cai (Frontiers in Genetics, 2022)
Background: Karyopherin alpha (KPNA), a nuclear transporter, has been implicated in the development as well as the progression of many types of malignancies. Immune homeostasis is a multilevel system which regulated by multiple factors. However, the functional significance of the KPNA family in the pathogenesis of lung adenocarcinoma (LUAD) and the impact of immune homeostasis are not well characterized.Methods: In this study, by integrating the TCGA-LUAD database and Masked Somatic Mutation, we first conducted an investigation on the expression levels and mutation status of the KPNA family in patients with LUAD. Then, we constructed a prognostic model based on clinical features and the expression of the KPNA family. We performed functional enrichment analysis and constructed a regulatory network utilizing the differential genes in high-and low-risk groups. Lastly, we performed immune infiltration analysis using CIBERSORT.Results: Analysis of TCGA datasets revealed differential expression of the KPNA family in LUAD. Kaplan-Meier survival analyses indicated that the high expression of KPNA2 and KPNA4 were predictive of inferior overall survival (OS). In addition, we constructed a prognostic model incorporating clinical factors and the expression level of KPNA4 and KPNA5, which accurately predicted 1-year, 3-years, and 5-years survival outcomes. Patients in the high-risk group showed a poor prognosis. Functional enrichment analysis exhibited remarkable enrichment of transcriptional dysregulation in the high-risk group. On the other hand, gene set enrichment analysis (GSEA) displayed enrichment of cell cycle checkpoints as well as cell cycle mitotic in the high-risk group. Finally, analysis of immune infiltration revealed significant differences between the high-and low-risk groups. Further, the high-risk group was more prone to immune evasion while the inflammatory response was strongly associated with the low-risk group.Conclusions: the KPNA family-based prognostic model reflects many biological aspects of LUAD and provides potential targets for precision therapy in LUAD.